Development of real-time PCR methods for cocoa authentication in processed cocoa-derived products. (January 2022) - de Oliveira, Ana Caroline; Marien, Aline; Hulin, Julie; Muhovski, Yordan; Baeten, Vincent; Janssen, Eric; Berben, Gilbert; Rogez, Herve; Debode, Frédéric
Abstract: The applicability of real-time PCR to highly processed cocoa-derived products for authentication purposes depends on the possibility of extracting high quality DNA and developing efficient PCR tests. This study compares three methods for DNA extraction from cocoa-derived products and chocolate. The best method providing suitable DNA for PCR amplification was the classical CTAB method. Seven real-time PCR tests for cocoa detection were designed based on low (nuclear) and high-copy (ribosomal and chloroplast) DNA targets. Two methods, one based on a nuclear target (vicilin-li PCR test) and a second one based on chloroplast DNA (lipids PCR test), successfully passed the performance criteria considering the specificity, sensitivity, efficiency of amplification, robustness and applicability in processed cocoa-derived products and chocolate. Therefore, this methodology is useful for cocoa authentication purposes and constitutes a first step in the direction of a future distinction between fine and bulk genotypes with an easy, fast and cost-effective methodology. Highlights: Three DNA extraction methods were compared on cocoa-derived products. The CTAB method was considered as the most suitable. The CTAB method allowed amplifiable cocoa DNA to all the processed samples tested. Two real time PCR based on nuclear and cpDNA were specific for cocoa detection. PCR tests were sensitive, efficient, robust and applicable for cocoa products.